EFFECTS OF PROTEIN-ENERGY MALNUTRITION ON THE IMMUNE SYSTEM - Amir, Mellova Amir (Makara Journal of Science, 2003)
Protein-Energy Malnutrition (PEM) is believed to lead to an increased susceptibility to infection, or cause impaired immunity. Infection, occurring with malnutrition, is a major cause of morbidity in all age groups and is responsible for two-thirds of all death under 5 yr of age in developing countries. Many cells of the immune system are known to depend for their function on metabolic pathways that employ various nutrients as critical factors. The most consistent changes in immune competence in PEM are in cell-mediated immunity, the bactericidal function of neutrophils, the complement system, the secretory immunoglobin A, and antibody response